2016
DOI: 10.1039/c6ra23742h
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized α,β-ynones: efficient ligand for Cu catalyzed Sonogashira-type cross-coupling reaction

Abstract: 1,3-Yones as σ-, π-electron donating ligands significantly accelerated the cross-coupling reactions of aryl iodides with terminal alkynes, in which as low as 0.1 to 1 mol% of CuI were efficiently activated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…In this field there are two main types of dipoles, pyridinium-type and iminoester-derived ylides. 452 Pyridinium (566), quinolinium (567), and isoquinolinium (568) salts are precursors of the corresponding Caira and co-workers 453 have described the three-component synthesis of pyrrolo[1,2-a]quinoline derivatives (572) by reaction of quinoline with phenacyl bromides and ynones 71 in the presence of propylene oxide. In these processes, quinolinium salts 567 (R = PhCO) were generated and the bromide opens the epoxide giving the corresponding alkoxide, which acted as a base generating ylides 570.…”
Section: [2 + 2]mentioning
confidence: 99%
See 2 more Smart Citations
“…In this field there are two main types of dipoles, pyridinium-type and iminoester-derived ylides. 452 Pyridinium (566), quinolinium (567), and isoquinolinium (568) salts are precursors of the corresponding Caira and co-workers 453 have described the three-component synthesis of pyrrolo[1,2-a]quinoline derivatives (572) by reaction of quinoline with phenacyl bromides and ynones 71 in the presence of propylene oxide. In these processes, quinolinium salts 567 (R = PhCO) were generated and the bromide opens the epoxide giving the corresponding alkoxide, which acted as a base generating ylides 570.…”
Section: [2 + 2]mentioning
confidence: 99%
“…This transformation requires the use of an equimolecular amount the copper(I) salt. 567 Yadav and co-workers reported on the reaction of electronrich arenes with ynones (71) catalyzed by gallium(III) chloride, which gave the corresponding (E)-enones (236) in good yield as the only product (Scheme 368). 568 α,α-Dibromoketones (224, easily obtained from ethyl acetylene carboxylates; Scheme 99, section 2.4.2) can be transformed into the corresponding silyl enol ethers (825) and 1-(1-alkynyl)-2,2-dibromovinyl acetates 826 in good yields (Scheme 369).…”
Section: Other Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al used functionalized α,β-ynones as efficient ligand for Cu catalyzed Sonogashira-type cross-coupling reaction. 44 Usually Csp 2 –Csp cross coupling requires considerable excess of copper catalyst and N, O donor ligands under the typical reaction condition. In this method, they utilized α,β-ynones as an efficient ligand system and found that substituted alkynes, at low-mol percent catalyst system demonstrated adequate activity and tolerance.…”
Section: Homogeneous Copper Catalystsmentioning
confidence: 99%